Bupropion - an antidepressant drug with broad therapeutic potential - Bróż, Sebastian; Dankiewicz, Sara; Żelazny, Przemysław; Filipczak, Joanna; Swora, Aleksandra; Borowik, Joanna; Sygacz, Oliwer; Brodowski, Wojciech; Pawłowski, Piotr; Basta-Arciszewska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Bupropion is currently mainly used as an atypical antidepressant due to its psychotropic effects. In addition, it shows high potential in reducing withdrawal cravings in addicts, which is also used in the treatment of nicotinism. However, studies in recent years have shown that it may also be useful in other conditions. Aim of the study: Our aim was to review the known usage of bupropion in the fields of psychiatry, neurology and internal medicine, and to identify potential directions for further research. Methods and materials: We reviewed the literature available in the PubMed database, using the key words: "bupropion"; "depression"; "smoking cessation"; "obesity"; "ADHD". Results: Bupropion- an antidepressant drug belonging to the group of selective norepinephrine and dopamine reuptake inhibitors. Bupropion is approved by the FDA(Food and Drug Administration) for the treatment of depression, seasonal affective disorder and nicotinism. The literature shows that it is also effective in off-label indications - treatment of antidepressant-induced sexual dysfunction, attention deficit hyperactivity disorder (ADHD), depression in bipolar disorder, obesity, neuropathic pain and cancer-related fatigue syndrome. Conclusion: Due to the specific effects of bupropion, there are many more usage for the drug than the primary indications for which it is usually used. The usage of the drug described in the literature require additional studies on a larger group of patients.